Using systems thinking to inform management of imperiled species: A case study with sea turtles. (August 2021) - Silver-Gorges, Ian; Ceriani, Simona A.; Ware, Matthew; Lamb, Megan; Lamont, Margaret; Becker, Janice; Carthy, Raymond R.; Matechik, Chris; Mitchell, Joseph; Pruner, Raya; Reynolds, Mike; Smith, Bradley; et al.
Abstract: Management of imperiled species facing spatiotemporally dynamic threats is difficult. Systems thinking can inform their management by quantifying the impacts that they face. We apply systems thinking to the Northern Gulf of Mexico (NGM) loggerhead ( Caretta caretta ) Recovery Unit (RU), one of the smallest subpopulations of loggerheads nesting in the USA. We characterized disturbances to nests, management actions, and hatchling production across 12 nesting beaches used by this RU to explore how hatchling production would increase if disturbances were mitigated. Annual hatchling production at sites ranged from 470 to 18, 191 hatchlings/year. Washovers (19.3% nests/year), washouts (17.9% nests/year), and predation (13% nests/year) were the most common annual disturbances across sites. Focusing on the most impactful disturbances at just five sites could increase annual NGM RU hatchling production by 2.2–6.7%. Efforts to mitigate washovers and washouts are ongoing in Alabama, but these may be futile against tropical cyclones, which accounted for >80% of washouts in the present study, and further require careful examination of associated adverse side-effects. Efforts to mitigate predation are common throughout this RU, but require improved knowledge of predator ecology to reach full potential. Systems thinking allowed us to create a simple model for assessing disturbances and management strategies in terms of hatchling sea turtles. This model can be augmented to run dynamic simulations of how disturbances and management actions impact hatchling production, and can be applied to other species with similar reproductive strategies. Highlights: Sea turtle nesting beaches are managed to maximize hatchling production. Systems thinking can help quantify how disturbances impact hatchling production. Managers can take actions to mitigate most impactful disturbances. Nesting beaches in the Northern Gulf of Mexico require tailored management. Management tailored to individual beaches can contribute to regional management.